2008
DOI: 10.1038/nphys1032
|View full text |Cite
|
Sign up to set email alerts
|

Simulating a quantum magnet with trapped ions

Abstract: To gain deeper insight into the dynamics of complex quantum systems we need a quantum leap in computer simulations. We can not translate quantum behaviour arising with superposition states or entanglement efficiently into the classical language of conventional computers. The final solution to this problem is a universal quantum computer [1], suggested in 1982 and envisioned to become functional within the next decade(s); a shortcut was proposed via simulating the quantum behaviour of interest in a different qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
778
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 608 publications
(787 citation statements)
references
References 26 publications
(47 reference statements)
6
778
0
3
Order By: Relevance
“…Finally, the recent progress in the field of nanomechanical oscillators makes possible the study of frequency jumps in nanomechanical resonators 16 , which is predicted to be accompanied by squeezing 31 . Our work paves the way for further simulations of quantum coherence phenomena using superconducting quantum circuits 32,33 .…”
Section: Discussionmentioning
confidence: 89%
“…Finally, the recent progress in the field of nanomechanical oscillators makes possible the study of frequency jumps in nanomechanical resonators 16 , which is predicted to be accompanied by squeezing 31 . Our work paves the way for further simulations of quantum coherence phenomena using superconducting quantum circuits 32,33 .…”
Section: Discussionmentioning
confidence: 89%
“…The pioneering experiments were reported in Refs. [86,87]. While in the early theory studies [85,[88][89][90] spin interactions decaying with the third power of the distance were considered, it was experimentally demonstrated that management of phonon dispersion allows to achieve powers between 0.1 and 3 in the 2D arrays of traps [91].…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the experimental protocol for our feasibility study in the case of two spins is realized in the following way and is further described in [3] and illustrated in Fig. 6.…”
Section: Simulating the Quantum Magnetmentioning
confidence: 99%
“…5 of the final state after the phase-gate operation. Figure 7 depicts the probability to detect both spins in the same state after steps (1,2,3,4,5) of the protocol for the QS described above. Since the initialized state |→→ can be rewritten in our measurement basis (omitting normalization factors) as (|↓ + |↑ )(|↓ + |↑ ) = (|↓↓ + |↓↑ + |↑↓ + |↑↑ ), we expect already a 50% probability P ↓↓ + P ↑↑ to project this state in either |↓↓ or |↑↑ .…”
Section: Simulating the Quantum Magnetmentioning
confidence: 99%
See 1 more Smart Citation